Non-governmental organizations in transforming the agri-business scenario - Saxena, Raka; Singh, Ritambhara; S, Raman M (Indian Farming, 2021)
Non-Governmental Organizations (NGOs) are the non-profit organizations which function independently. Their concept was first introduced in Article 71 of the newly formed United Nations Charter, 1945. NGOs may serve at community, national and international levels for meeting various goals related to social welfare, humanitarian causes, environment, agricultural development, research and consulting and may perform many other service functions. They may receive funding from various national and international sources including Governments, foundations, corporates, etc. Task-oriented and made up of people with a common interest, NGOs perform a variety of services and humanitarian functions, bring citizen’s concerns to Governments, monitor policy and program implementation, and encourage participation of civil society stakeholders at the community level. NGOs, as perceived to be directly connected to the grassroot level, facilitate economic development in several ways and may lead to closer convergence in the macro-level policy formulation and micro-level development needs.